Bulk sediment element concentrations and biogenic barium of IODP Site U1537 - Hallmaier, Moritz; Gutjahr, Marcus; Lippold, Jörg; Hemming, Sidney R; Gerber, Lukas; Weber, Michael E; Eisenhauer, Anton (In: Hallmaier, M et al. (2025): Authigenic Uranium Preservation and Bottom Water Oxygenation in the Scotia Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982959, 2025)
Bulk element concentrations were measured for a subset of samples on aliquots after digestion on an ICP-OES (Agilent 700 Series) at the Institute of Earth Sciences, Heidelberg University. Biogenic Barium (Babio) was calculated from Ba and Al concentrations following Nürnberg et al. (1997) with a detrital Ba/Al factor of 0.0067. Biogenic barium fluxes were calculated by 230Th normalization.
Keywords: authigenic uranium; Biogenic Barium (xsBa); bottom-water oxygenation; export productivity; opal; Scotia Sea; sediment; Southern Ocean; Th; thorium normalization; Weddell Sea